045 We're going to need a bigger boat! Evening opening of mothballed outpatient areas to reduce crowding in a children's emergency department. Issue 12 (21st November 2019) - Hance, Katherine; Lyttle, Mark; Humphreys, Sue
Abstract : Background: EDs are increasingly crowded, with negative impact on care quality. This is multifactorial, but tends to peak during evenings. On mapping our contributing constraints, staffing was adequate, but available ED space was a major factor. We identified evening opening of mothballed clinical areas as a potential strategy, of which one was our outpatient department (OPD); housed one minute away on the same floor this closes at 1700. Through the 2018/19 winter this opened between 1800–2330; we evaluated impact on service provision and staff morale. Method and results: Continuous PDSA cycles were initiated; a living standard operational policy evolved based on staff/patient feedback. Flow and patient acuity markers were monitored using electronic tracking systems. Staff were surveyed to explore opinions and impact on morale. Conclusions: During November 2018–April 2019 the OPD opened on 76 days (50%), with 1082 patients seen. Opening was more frequent during November-February; during peak activity >10% all daily attendances were seen in this stream. Mean time to see clinicians was 77 minutes and mean time to discharge was 133 minutes; both compared favourably with patients remaining in ED. This partly reflects lower patient acuity, but other crowding measures including total patients in department, and total patient minutes, also improved. The most common diagnoses were soft tissue injury, fracture, head injury, and URTI. No safety incidents occurred and <1% left without being seen. Staff feedback reflected increased morale, and lower stress and noise levels during peak activity. Novel use of mothballed clinical areas during peak ED activity is an attractive option for families and staff, and appears to improve safety and effectiveness. Use of existing staff was cost effective, with total additional cost pressures for nurses (£20K) and support staff (£500), in comparison to projected costs of £100K for one embedded evening GP over the same period.